2002
DOI: 10.1046/j.1365-2141.2002.03441.x
|View full text |Cite
|
Sign up to set email alerts
|

Mean platelet volume is an independent risk factor for myocardial infarction but not for coronary artery disease

Abstract: Summary. After rupture of an arteriosclerotic plaque in a coronary artery, platelets play a crucial role in the subsequent thrombus formation, leading to myocardial infarction. An increased mean platelet volume (MPV), as an indicator of larger, more reactive platelets, may represent a risk factor for myocardial infarction. However, this hypothesis is still controversial and most studies addressing the role of MPV were performed comparing patients suffering from myocardial infarction with healthy controls. We i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
336
4
24

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 442 publications
(380 citation statements)
references
References 33 publications
16
336
4
24
Order By: Relevance
“…40 recently, the MPV has been the subject of significant research among adult patients with cardiovascular diseases, establishing that higher MPVs identify patients more likely to have poorer outcome after an acute vascular event. [43][44][45] It has been proposed in these patients that a larger MPV is an indicator of increased platelet activation. 46 The paucity of gestational age-based normative data has limited the clinical utility of MPVs in neonatal medicine.…”
Section: Discussionmentioning
confidence: 99%
“…40 recently, the MPV has been the subject of significant research among adult patients with cardiovascular diseases, establishing that higher MPVs identify patients more likely to have poorer outcome after an acute vascular event. [43][44][45] It has been proposed in these patients that a larger MPV is an indicator of increased platelet activation. 46 The paucity of gestational age-based normative data has limited the clinical utility of MPVs in neonatal medicine.…”
Section: Discussionmentioning
confidence: 99%
“…From earlier studies such as by Endler et al [1], we see that higher cut-off such as 11.6 have been used and this has been shown to be an independent risk factor. However in our observation we find that a very small number of patients had MPV values more than 11.…”
Section: To the Editormentioning
confidence: 99%
“…Significant risk factors such as diabetes, hypertension, smoking, hypercholesterolemia and lifestyle have been already studied. Mean platelet volume (MPV) has been found to be an independent risk factor in western populations and also from Indian Data [1][2][3]. Hence we thought it appropriate to look at this parameter in Indian patients with history of MI or CAD.…”
Section: To the Editormentioning
confidence: 99%
“…Large platelets have higher thrombotic potential [11] and express higher levels of P-selectin [12] and glycoprotein IIbIIIa [13] than small platelets. Several studies have shown increased MPV in patients with coronary artery disease [14,15], and MPV has been identified as an independent risk factor for myocardial infarction and stroke [16][17][18].…”
Section: Introductionmentioning
confidence: 99%